Narrative and Numbers : The Value of Stories in Business - Damodaran, Aswath (Columbia Business School Publishing, 2017)
How can a company that has never turned a profit have a multibillion dollar valuation? Why do some start-ups attract large investments while others do not? Aswath Damodaran, finance professor and experienced investor, argues that the power of story drives corporate value, adding substance to numbers and persuading even cautious investors to take risks. In business, there are the storytellers who spin compelling narratives and the number-crunchers who construct meaningful models and accounts. Both are essential to success, but only by combining the two, Damodaran argues, can a business deliver and sustain value.Through a range of case studies, Narrative and Numbers describes how storytellers can better incorporate and narrate numbers and how number-crunchers can calculate more imaginative models that withstand scrutiny. Damodaran considers Uber's debut and how narrative is key to understanding different valuations. He investigates why Twitter and Facebook were valued in the billions of dollars at their public offerings, and why one (Twitter) has stagnated while the other (Facebook) has grown. Damodaran also looks at more established business models such as Apple and Amazon to demonstrate how a company's history can both enrich and constrain its narrative. And through Vale, a global Brazil-based mining company, he shows the influence of external narrative, and how country, commodity, and currency can shape a company's story. Narrative and Numbers reveals the benefits, challenges, and pitfalls of weaving narratives around numbers and how one can best test a story's plausibility.